Significance of serum branched-chain amino acid to tyrosine ratio measurement in athletes with high skeletal muscle mass - Katsuhiko Tsunekawa; Ryutaro Matsumoto; Kazumi Ushiki; Larasati Martha; Yoshifumi Shoho; Yoshimaro Yanagawa; Hirotaka Ishigaki; Akihiro Yoshida; Osamu Araki; Kiyomi Nakajima; Takao Kimura; Masami Murakami (BMC, 2021)
Abstract Background Few nutritional markers reflect the hypermetabolic state of athletes with high levels of skeletal muscle. Although branched-chain amino acids (BCAA) play crucial roles in protein metabolism in skeletal muscle, the relationship between skeletal muscle mass and amino acid imbalances caused by the metabolism of BCAA and aromatic amino acids remains unclear. The aim of this study is to test the hypothesis that athletes with high levels of skeletal muscle mass have plasma amino acid imbalances, assessed by serum BCAA to tyrosine ratio (BTR) which can be measured conveniently. Methods The study enrolled 111 young Japanese men: 70 wrestling athletes and 41 controls. None of them were under any medications, extreme dietary restrictions or intense exercise regimens. Each participant's body composition, serum concentrations of albumin and rapid turnover proteins including transthyretin and transferrin, BTR, and thyroid function were assessed. Results Compared to the controls, the athletes had significantly higher skeletal muscle index (SMI) (p < 0.001), and lower serum albumin concentration (p < 0.001) and BTR (p < 0.001). Kruskal-Wallis tests showed that serum albumin concentration and BTR were significantly lower in the participants with higher SMI. Serum albumin concentration and BTR were inversely correlated with SMI by multiple regression analysis (logarithmic albumin, β = − 0.358, p < 0.001; BTR, β = − 0.299, p = 0.001). SMI was inversely and transthyretin was positively correlated with serum albumin (SMI, β = − 0.554, p < 0.001; transthyretin, β = 0.379, p < 0.001). Serum concentration of free 3,5,3'-triiodothyronine (FT3) was inversely correlated with BTR, and, along with SMI and albumin, was independent predictor of BTR (SMI, β = − 0.321, p < 0.001; FT3, β = − 0.253, p = 0.001; logarithmic albumin, β = 0.261, p = 0.003). However, FT3 was not correlated with SMI or serum albumin. Serum concentrations of rapid turnover proteins were not correlated with BTR. Conclusions Increased skeletal muscle mass enhances the circulating amino acid imbalances, and is independently facilitated by thyroid hormones. Serum BTR may be a useful biomarker to assess the hypermetabolic state of wrestling athletes with high levels of skeletal muscle.